Conservative esthetic solution with ceramic laminates: literature review - Gisely Naura Venâncio; Rosceline Rodrigues Guimarães Júnior; Sybilla Torres Dias (Revista Sul-Brasileira de Odontologia, 2015)
Modern dentistry seeks to offer increasingly esthetic treatments, aimed at patient’s well-being and satisfaction. In this perspective, this study aimed to conduct a literature review on the use of ceramic laminates as conservative and esthetic solution, addressing their indications, contraindications, limitations and its importance in dentistry. Literature review: The evidence in the literature show that the ceramic laminates are used for restoring anterior teeth, reestablishing dental function and esthetic mainly due to its excellent optical property, and preserving tooth structure, as it is necessary less tooth wear to return shape, texture, color and harmony to the teeth involved. Conclusion: It was conclude that this is a treatment option with high success rate when properly indicated, planned and executed according to each case.